1996
DOI: 10.3109/00207459608987253
|View full text |Cite
|
Sign up to set email alerts
|

Emotion-Specific Processing Deficit in Focal Brain-Damaged Patients

Abstract: Focal brain-damaged patients (left hemisphere damage, right hemisphere damage) and hospitalized general medical patients were asked to sort test photographs into target expressions of four facial emotions, happy, sad, fear and anger. In a second task, patients were asked to match neutral photographs with these target emotion expressions in a forced-choice format. Patients were also asked to rate their mood state on a two-dimensional affect grid. Right hemisphere-damaged patients were significantly inaccurate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…According to the right hemisphere hypothesis of emotion, the right hemisphere of the brain is specialized for emotional and the left for cognitive processes [2], [3]. This hypothesis is supported by findings from behavioral [2], [4] and lesion studies [5] although conflicting findings have been reported [6], [7], [8].…”
Section: Introductionmentioning
confidence: 86%
“…According to the right hemisphere hypothesis of emotion, the right hemisphere of the brain is specialized for emotional and the left for cognitive processes [2], [3]. This hypothesis is supported by findings from behavioral [2], [4] and lesion studies [5] although conflicting findings have been reported [6], [7], [8].…”
Section: Introductionmentioning
confidence: 86%
“…C. Borod, et al, 1998; J.C. Borod, Koff, Perlman, & Nicholas, 1986;Charbonneau, Scherzer, Aspirot, & Cohen, 2003;Zgaljardic, Borod, & Sliwinski, 2002). However, several studies have also indicated that left hemisphere lesions can sometimes result in impaired EP (Braun, Traue, Frisch, Deighton, & Kessler, 2005;Mandal, Mohanty, Pandey, & Mohanty, 1996). For ToM, some previous studies have reported that right hemisphere damage impairs (cognitive) ToM more than left hemisphere damage (Griffin, et al, 2006;F.…”
Section: Lesion Study Data On the Relationship Between Emotion Percepmentioning
confidence: 99%
“…In its earliest form, this hypothesis highlighted a critical role for the RH in all aspects of emotion processing, including both positive and negative emotions. For example, behavioral studies in humans have shown that emotions are expressed more intensely on the left side of the face (Sackeim & Gur, 1978) and that RH damage has been associated with impaired recognition of facial expressions of emotion (Mandal, Mohanty, Pandey, & Mohanty, 1996). It should be noted that not all studies have demonstrated a reliable emotion-RH link (Mandal, Asthana, Tandon, & Asthana, 1992), and interested readers are referred to the following source for further reading in this area (Borod, Zgaljardic, Tabert, & Koff, 2001).…”
Section: Single-system Models Of Emotionmentioning
confidence: 99%